Phytochemical screening and comparative study of antibacterial assays of carum roxburghianum and trigonella foenum-graecum obtained grom plant seed - Amin, Fatima (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2016.